Multi-omics integrated analyzed the origin of intrahepatic mucinous cholangiocarcinoma: a case report - Zeng, Xiaokang; Ou, Huohui; Zeng, Chong; Liu, Qingbo; Wang, Weidong; Yao, Jie (Frontiers in Oncology, 2023)
Intrahepatic mucinous cholangiocarcinoma (IMCC) is a rare subtype of intrahepatic cholangiocarcinoma (IHCC). Limited data describe the genetic characteristics of IMCC and insights on its pathogenesis are lacking. Here, we employed a multi-omics approach to analyze somatic mutations, transcriptome, proteome and metabolome of tumor tissue obtained from a case of IMCC in order to clarify the pathogenesis of IMCC. A total of 54 somatic mutations were detected, including a G12D mutation in KRAS that is likely to be involved in the onset of IMCC. The genes consistently up-regulated at the transcription level and in the proteome were enriched for mucin and mucopolysaccharide biosynthesis, for cell cycle functions and for inflammatory signaling pathways. The consistently down-regulated genes were enriched in bile 1 synthesis and fatty acid metabolism pathways. Further multi-omics analysis found that mucin synthesis by MUC4 and MUC16 was elevated by up-regulated expression of mesothelin (MSLN). Moreover, transcription factor ONECUT3 was identified that possibly activates the transcription of mucin and mucopolysaccharide biosynthesis in IMCC.